Hubungan Lingkungan Fisik, Kimia dan Biologi dengan Kepadatan vektor Anopheles di Wilayah Kerja Puskesmas Hamadi Kota Jayapura - Renold Markus Mofu (Jurnal Kesehatan Lingkungan Indonesia, 2013)
Background:According to 2010 Annual Parasite Incidence (API) report mortality rate caused by malaria inIndonesia was 1.3% in the ratio of 24/1000 population. Of these figures the 2011 Annual API report showed thatPapua Province had the malaria-caused mortality rate 181.85/1000 population, Jayapura Municipality 57.29/1000, and Hamadi Public Health Center 315/1000 population.This research aimed to find out the correlation ofphysical, chemical and biological factors to Anopheles vector density and to find out the vector densities ofAnopheles, Anopheles species, and the presence of sporozoit.Method: It was an observational research using case control design. There were 102 respondents used, consistingof 51 malaria casse and 51 controls. They were selected by a simple random sampling method. Statistical analysisused Pearson and Spearman tests, followed by Linear Regression test.Result: The results showed that there was a correlation of water pH (r = 0.799; 0.836), air temperature, windspeed (r = -0.68; 0.754) to vector density. Multivariate analysis showed that variables that became risk factor ofthe vector density were water body, air humidity (p = 0.009; 0.004). The research recorded that koliensis dominatedthe proportion of the Anopheles species (96.6% of the species found), whereas the smallest number by species wasfarauti (0.5%), with the density average of 2.1 individual/responden/hour.Conclusion:The largest number of sporozoit found was Plasmodium falciparum (25%). It was recommended to doenvironmental modification and manipulation and comprehensive and longitudinal studies of to reduse riskfactors of the Anopheles density. Keywords: physical, chemical, biological environments; Anopheles density.